Association between drinking patterns and cardiovascular risk: a population-based study in the Southern Cone of Latin America - Gulayin, Pablo Elías (2020)
Background Using data from general adult population, this study aims to describe epidemiology of alcohol consumption patterns and their association with cardiovascular risk. Methods CESCAS I is a population-based study from four mid-sized cities in Argentina, Chile and Uruguay. Associations between diabetes, hypertension, dyslipidemia, cardiovascular disease (CVD) risk and history of CVD and drinking patterns were assessed using crude prevalence odds ratios (ORs) and adjusted OR. Results A total of 37.2% of the studied population never drank and 18.3% reported to be former drinkers. Among current drinkers, moderate drinking was the most frequent pattern (24.2%). For women with light and moderate consumption, the odds of having >20% CVD risk was ~40% lower than that of never drinkers. The odds of having a history of CVD was 50% lower in those with moderate consumption. For men with heavy consumption, the odds of having >20% CVD risk was about twice as high as for never drinkers. Conclusions A harmful association was observed between heavy drinking and having >20% CVD risk for men. However, for women, an apparently protective association was observed between light and moderate drinking and having >20% CVD risk and between moderate drinking and having a history of CVD.